2020
DOI: 10.1080/02656736.2019.1710269
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between induction heating, antibiotics, and N-acetylcysteine eradicates Staphylococcus aureus from biofilm

Abstract: Background: Non-contact induction heating (NCIH) is a noninvasive treatment modality that can be used to cause thermal damage to bacterial biofilms on a metal implant surface in the context of a prosthetic joint infection. The purpose of this study was (1) to determine the effectiveness of NCIH on killing Staphylococcus aureus from biofilm and (2) to determine the possible synergistic effect of NCIH and cocktails of antibiotics and N-acetylcysteine (NAC). Methods: Staphylococcus aureus biofilms were grown on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 34 publications
4
26
0
1
Order By: Relevance
“…Results showed a temperature-dependent reduction in bacterial counts in immature biofilms with complete bacterial eradication seen at a surface temperature of 85 °C, whereas bacterial counts in mature biofilms decreased in a temperaturedependent fashion up to 70 °C and thereafter remained unchanged. The observed effect of NCIH on immature biofilms is in line with an earlier observation that almost all bacteria within 24 h biofilms are eliminated by a heat shock of 85 °C (Pijls et al, 2020). The difference in susceptibility of bacteria in mature and immature biofilms to induction heating could be related to the amount of protective extracellular matrix, which is considerably larger in mature biofilms.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Results showed a temperature-dependent reduction in bacterial counts in immature biofilms with complete bacterial eradication seen at a surface temperature of 85 °C, whereas bacterial counts in mature biofilms decreased in a temperaturedependent fashion up to 70 °C and thereafter remained unchanged. The observed effect of NCIH on immature biofilms is in line with an earlier observation that almost all bacteria within 24 h biofilms are eliminated by a heat shock of 85 °C (Pijls et al, 2020). The difference in susceptibility of bacteria in mature and immature biofilms to induction heating could be related to the amount of protective extracellular matrix, which is considerably larger in mature biofilms.…”
Section: Discussionsupporting
confidence: 89%
“…To heat up the TAN discs in a controlled fashion, a miniaturised version of the NCIH apparatus was built and successfully validated. This equipment was designed to reach a target temperature rather than to maintain the temperature for a prolonged period, as was the case in previous NCIH studies (Pijls et al, 2020). The rationale for this approach was twofold.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study in 2017, Ricker and Nuxoll [31] investigated the synergistic effects of heat and antibiotics using ciprofloxacin, tobramycin and erythromycin on P. aeruginosa strains and they reported that combined treatments had synergistic effects for heat shock conditions of 60 C for 5 min to 70 C for 1 min. Recently, Pijls et al [32] investigated the synergistic effects of non-contact induction heating and antibiotic cocktails and reported that a combination of heat plus antibiotics had synergistic effects on Staphylococcus aureus biofilms at 60 C. Both studies achieved promising results; however; they performed their research at high temperatures, which may cause thermal damage to human tissue. Wu et al [33] designed a magnetic nanoparticle platform to investigate the synergistic effects of nanoparticle heating and the antimicrobial drug amoxicillin on H. pylori and reported that this combination increased the susceptibility of H. pylori to amoxicillin due to the destruction of the cell membrane and microbial biofilm at 41 C. In contrast to our study, they used amoxicillin-loaded nanoparticles in their research.…”
Section: Colony Counts At 1st Hourmentioning
confidence: 99%